BandÄ«Å›-s in khayÄl of Indian classical music: a study of selected song-texts with special reference to the bandÄ«Å›-s of sadÄraá¹‡g in Hindustani music - Bilambita Banisudha (International Journal of Visual and Performing Arts, 2022)
Melody is the soul of Indian classical music. A musician presents different captivating melodic motions of a certain set of notes, showing their diverse permutations and combinations as well as their hidden beauty. This melodic exposition decorates the mind with several melodic expressions and embellishments and is hence referred to as RÄg â€“ which brings aesthetic pleasure. The main objective of this research is the presentation and style of certain rags, as well as the improvisation of the melodic structure. The data obtained by recording the song's melody audio technique and watching the concert live and all of them will be used to analyze and check the composition of the song. The musical analysis is carried out with respect to RÄg. This is because a composition like a mirror reflects a complete picture of an RÄg. It reveals and also retains its characteristics, such as its ascending and descending notes, its dominating notes, other sub-dominant notes, its intricacies, and its special combination of notes, i.e., svara-saÃ±gati. The different BandÄ«Å›-s in an RÄg highlight the different aspects and shades in which it can be rendered. The results of this study indicate that compositions in Indian music are a combination of traits that includes the aspects of the musical structure, vocal style and techniques, instrumentation, rhythmic style, and poetry. BandÄ«Å› in KhyÄl of Hindustani music refers to the text of the composition. The text is marked by the elegant use of words. The musical structure of BandÄ«Å›-s is comprised of certain essential laya (Tempo), tÄl (beat), RÄg (melody), and dhÄtu-s (the melodic component)